Splicing regulators and their roles in cancer biology and therapy - Silva, Maria Roméria da; Moreira, Gabriela Alves; Silva, Ronni Anderson Gonçalves da; Barbosa, Éverton de Almeida Alves; Siqueira, Raoni Pais; Teixera, Róbson Ricardo; Almeida, Márcia Rogéria; Silva Júnior, Abelardo; Fietto, Juliana Lopes Rangel; Bressan, Gustavo Costa (BioMed Research International, 2015)
Alternative splicing allows cells to expand the encoding potential of their genomes. In this elegant mechanism, a single gene can yield protein isoforms with even antagonistic functions depending on the cellular physiological context. Alterations in splicing regulatory factors activity in cancer cells, however, can generate an abnormal protein expression pattern that promotes growth, survival, and other processes, which are relevant to tumor biology. In this review, we discuss dysregulated alternative splicing events and regulatory factors that impact pathways related to cancer. The SR proteins and their regulatory kinases SRPKs and CLKs have been frequently found altered in tumors and are examined in more detail. Finally, perspectives that support splicing machinery as target for the development of novel anticancer therapies are discussed.
Keywords: Splicing regulators; Cancer; Therapy